Negara Pancasila dalam Perspektif Muhammadiyah dan Nahdlatul Ulama sebagai Landasan Keislaman Kebangsaan dan Kehidupan Bernegara - Dini Stevani Damaiyanti; Syifa Azzahra; Dzalfa Dzahhabiah Putri; Nailah Nailah; Surya Sukti (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This article discusses the concept of the Pancasila State from the perspective of Muhammadiyah and Nahdlatul Ulama with the aim of understanding the relationship between Islam and the state, relevant Islamic jurisprudence principles, and the role of Islamic organizations in national life. The research method used is qualitative with a descriptive-analytical approach, utilizing literature studies from books, journals, and official organizational documents. The results of the study indicate that Islam provides universal principles such as justice, deliberation, and welfare, which can be applied in various state systems without having to take the form of a formal Islamic state. Muhammadiyah defines the state through the concept of Darul Ahdi wa Syahadah, emphasizing rationality, modernity, and the implementation of Islamic values in education, social, and societal progress. Meanwhile, Nahdlatul Ulama, through the principle of Hubbul Wathan Minal Iman and the concept of Islam Nusantara, emphasizes harmony between Islamic teachings, local traditions, and nationality, as well as moderation in socio-political life. These differences in approach are not a source of conflict, but rather complement each other in maintaining stability, tolerance, and the welfare of the nation. This study confirms that the Pancasila State possesses both constitutional and religious legitimacy, and that both Muhammadiyah and Nahdlatul Ulama play a crucial role in maintaining the integration of Islamic and national values. These findings demonstrate that the acceptance of Pancasila by these two major Islamic organizations in Indonesia is not merely formal but also based on theological ijtihad and Islamic jurisprudence (fiqh) principles that adapt to Indonesia's socio-cultural context. This study is expected to serve as a reference in developing contextual and inclusive studies of the relationship between religion and state in Indonesia.